2017
DOI: 10.5539/jas.v9n10p85
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of N and K Fertilizers on Yield and Components of Soybean (Glycine max (L.) Merr.)

Abstract: Nitrogen and potassium fertilization have given variable results in increasing soybean yield. More information is needed about optimum potassium (K) and nitrogen (N) fertilizers placement for soybean. This study investigated the effect of different amounts of nitrogen and potassium on yield and its components on soybean cultivar DPX. Treatments include nitrogen (from urea) -Potash (potassium sulfate) in seven levels (N0-K0, N50-K0, N0-K20, N50-K20, N100-K50, N200-K100 and N250-K150 kg/ha) and factor inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Nitrogen is the most important nutrient for the synthesis of proteins and the enhancement nutrient content in the leaves of plant including nitrogen and potassium content [18]. The obtained data was in accordance with those previously reported by authors [51,52] who reported that N-fertilizer increased the leaf nitrogen concentration.…”
Section: Resultssupporting
confidence: 90%
“…Nitrogen is the most important nutrient for the synthesis of proteins and the enhancement nutrient content in the leaves of plant including nitrogen and potassium content [18]. The obtained data was in accordance with those previously reported by authors [51,52] who reported that N-fertilizer increased the leaf nitrogen concentration.…”
Section: Resultssupporting
confidence: 90%
“…This suggests that yield components (NN, NP, SWP and TSW) are significant factors that contribute to the expression of SY potential. Several researchers, Boroomandan et al [10], Showkat and Tyagi [34] and Shahkoohmahally and Shahkoohmahally [35] found a positive and significant correlation between SY and NP and SY and TSW. What is the more negative but non-significant relationship between PC and OC indicates the opposite trend of the protein and oil accumulation in response to the increased N rate.…”
Section: Interaction Of Factors Affected Quantitative and Qualitativementioning
confidence: 99%
“…The reason for the high fertilizer application rates is unclear, but it can be caused by lack of knowledge among farmers or improper methods in applying fertilizers (Sheikh Davoodi & Houshyar, 2009). In Iran, research suggests that soya bean yields keep increasing at rates of nitrogen application even higher than the ones used here (Shahkoohmahally & Shahkoohmahally, 2017). This combined with the fact that fertilizers are subsidized in Iran (FAO, 2005) may suggest that a high fertilizer rate is a local economic optimum.…”
Section: Discussionmentioning
confidence: 82%